The Effect of Nickel Sulfate on Seed Germination and Development of Sprouts Pribrezhno-Water Plants - Yelena G. Krylova (Журнал Сибирского федерального университета: Серия Биология, 2010)
The effect of nickel sulfate on seed germination and initial stages of growth of near-shore aquatic plants seedlings belonging to different ecological groups has been studied. During germinating seeds of Sium latifolium L., Alisma plantago-aquatica L., Butomus umbellatus L. - helophyte and Scirpus sylvaticus L. - hygrophytes after cold damp stratification the highest final germination has been shown for Alisma plantago-aquatica. The most sensitive seeds were those of susak. However, the limit of toxicity of nickel for the germination of the plants seeds of this group was not revealed. The limit toxicity of nickel for the seeds of hygrophyte group ranged between 25 - 50 mg/l. The normal development of helophyte seedlings was observed in solutions with concentrations of 1-25 mg/l for porucheynik, 1 mg/l - for chastuhi and susak. In solutions with concentrations of 50 and 100 mg /l, features of necrosis of leaves and roots, as well as the destruction of chlorophyll in leaves were found. Normal development of hygrophyte seedlings proceeded only in the variant with the concentration of a 1 mg/l.